Penciptaan Seni Serat sebagai Ekspresi Visual Tembang Pangkur - Ninantry Nurkhalissa; Apika Nurani Sulistyati (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The phenomenon of deteriorating mental health in the student environment can cause bad possibilities such as depression, escape to alcohol and drugs, drop out, and even suicidal ideation. Things of a spiritual nature are much needed in youth who are prone to falling into negative problems. The creation of this Final Project work adapts the spiritual message of Tembang Pangkur as a neutralizer for deteriorating mental health among students into a work of visual art. The aim is to convey spirituality which is presented as a medium of education and awareness through textile artwork. The method used is the Gustami Creation Method which consists of three stages including the exploration stage, the design stage, and the embodiment stage. The exploration stage is carried out by observing and collecting data regarding students' mental health problems and their relation to spiritual awareness, adapting the spirituality contained in tembang pangkur into a visual form as a solution and educational media, and determining the concept of the work, namely the process of a spiritual journey, as well as exploring techniques, materials and visually through trials. The design stage is carried out by visualizing the concept into several design alternatives that consider aspects of creating art. The embodiment stage, realizing the selected design into a work of fiber art and holding an evaluation in the form of a Final Project exhibition. The creation of this Final Project is realized into three works entitled Dark Soul, Good and Bad, and Healing Soul. The three works are related to each other which describes the process of a spiritual journey. The form of the work is in the form of a wall hanging with latch hook and crochet techniques as the craft technique. The materials used besides cotton thread are wasted materials such as cloth from unused clothes, mask straps, and wooden sticks.